The power of fat and its adipose‐derived stromal cells: emerging concepts for fibrotic scar treatment - Spiekman, Maroesjka; Dongen, Joris A.; Willemsen, Joep C.; Hoppe, Delia L.; Lei, Berend; Harmsen, Martin C. (Journal of tissue engineering and regenerative medicine, 2017)
Lipofilling or lipografting is a novel and promising treatment method for reduction or prevention of dermal scars after injury. Ample anecdotal evidence from case reports supports the scar‐reducing properties of adipose tissue grafts. However, only a few properly controlled and designed clinical trials have been conducted thus far on this topic. Also, the underlying mechanism by which lipofilling improves scar aspect and reduces neuropathic scar pain remains largely undiscovered. Adipose‐derived stromal or stem cells (ADSC) are often described to be responsible for this therapeutic effect of lipofilling. We review the recent literature and discuss anticipated mechanisms that govern anti‐scarring capacity of adipose tissue and its ADSC. Both clinical and animal studies clearly demonstrated that lipofilling and ADSC influence processes associated with wound healing, including extracellular matrix remodelling, angiogenesis and modulation of inflammation in dermal scars. However, randomized clinical trials, providing sufficient level of evidence for lipofilling and/or ADSC as an anti‐scarring treatment, are lacking yet warranted in the near future. © 2017 The Authors Journal of Tissue Engineering and Regenerative Medicine Published by John Wiley & Sons Ltd